Optoelectronic properties and applications of graphene-based hybrid nanomaterials and van der Waals heterostructures. (September 2019) - Wang, Jingang; Mu, Xijiao; Sun, Mengtao; Mu, Tingjie
Abstract: In this paper, we review the optoelectronic properties and applications of graphene and graphene heterostructures in recent years. Graphene is a 2D crystal with a single atomic layer thickness consisting of sp 2 hybridized conjugated carbon atoms. Graphene's unique optical and electrical properties have led to its further development in the field of nanoscale optoelectronics. Graphene has extremely high carrier mobility and a wide range of photoelectric response characteristics in conventional semiconductor optoelectronic devices, such as silicon and GaAs. By changing the shape of a graphene structure and combining it with other nanomaterials, nano-optoelectronic devices based on graphene have greatly improved performance. Optoelectronic devices based on graphene have broad application prospects.